IMPLEMENTASI ANALISIS JABATAN DALAM MENINGKATKAN EFEKTIFITAS KERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT - Juntak . (Jurnal Paradigma (JP), 2017)
Implementation analysis Secretariat office of Kutai Barat has run accordance with the qualifications especially in the job requirements and job descriptions. Although there is still position occupied by several officials who has appropriate qualifications or requirements such as level of education, skills, experience, and rank as a requirement in the position has yet to be implemented properly and correctly. There are other indications that causes of application of job analysis are reflected in the distribution of tasks or the work.